Paradoxical leadership on employee voice behavior - Imtinan, Demitri Fauziyah Syifa; Widiasih, Puti Archianti (JURNAL SPIRITS, 2024)
The industrial world is currently facing an era of TUNA (Turbulency, Uncertainty, Novelty, Ambiguity), with many uncertain changes and rapid technological updates. This condition certainly challenges organizations to become more competitive, so implementing voice behavior has an important role in organizational sustainability. Voice behavior can be influenced by leadership, one of which is paradoxical leadership. This research aims to examine the influence of paradoxical leadership on voice behavior among employees in Jabodetabek. The subjects of this research were 261 employees consisting of 135 men and 126 women. The sampling technique used was the incidental sampling technique. The instruments used in this research are the Paradoxical Leadership Scale to measure paradoxical leadership and the Voice Behavior Scale to measure voice behavior. The data analysis technique used is regression testing using SPSS 25.0 for Windows applications. Based on the results of the data analysis, the values r2=0.282, β=0.252, and p<0.001 were obtained. These results indicate a positive and significant influence of paradoxical leadership on employee voice behavior. So, organizations with leaders who implement dualistic actions in meeting organizational demands and employee needs will produce employees with high enthusiasm to contribute by conveying their ideas, concepts, or concerns to the organization.